ETSET: Enhanced Tiny Symmetric Encryption Techniques to Secure Data Transmission among IoT Devices - et. al., S. Alexander Suresh SDB , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet of Things (IoT) is an assembly of physical devices or objects that link through the Internet to deliver interaction and communication among each other. In recent years, the growth of IoT is rapidly tremendous, and it starts to occupy people’s lives in many areas such as hospitals, homes, roads and much more. IoT devices and data transfer create many new threats to the data transfer between the connected IoT devices. Securing the data in the IoT environment is the most important concern. Due to the IoT devices’ computation complexity, a strong, lightweight security technique is proposed in this paper. This proposed technique is an Enhanced Tiny Symmetric Encryption Technique (ETSET). It is enhanced from the existing TEA (Tiny Encryption Algorithm). The major issue in TEA is, it uses the same key in all cycles of encryption and decryption. It can be broken using a related-key attack. The proposed ETSET changes the key generation in a dynamic approach for each cycle. ETSET also reduces the number of rounds and enhance dynamic bit shifting in each round. The proposed ETSET is implemented using JAVA and compared with TEA, XTEA. The results show that the proposed ETSET produces a better solution with respect to encryption and decryption time.